Illegal Veterinary Medicines Trade and Use: Threat to Animal and Public Health in the IGAD Region - IGAD Center for Pastoral Areas & Livestock Development (ICPALD) (IGAD Center for Pastoral Areas & Livestock Development (ICPALD), 2021)
Illegal veterinary medicines (expired, understrength, diluted, adulterated or fake) in the IGAD region were observed to have a negative impact on delivery of animal health, production and marketing, which in turn affects the local communities and economies, livelihoods, human and animal health, which causes poverty. The most frequently illegal (expired, understrength, diluted, adulterated or fake) veterinary medicines, as perceived by the supply chain stakeholders, were antibiotics, antihelmintics, trypanocidals, acaricides and vaccines. The estimated prevalence of illegal drugs as reported by different supply chain stakeholders in South Sudan ranged from 46.7-60%; in Uganda ranged from 1-33%; and in Sudan ranged from 5-21%.